Preoperative immunochemotherapy versus chemotherapy as first-line treatment for patients with stage I–IIIB small-cell lung cancer - Linhai Zhu; Jiacong Liu; Xuhua Huang; Jian Hu (BMC Cancer)
Abstract Background To date, there remains a paucity of comparative investigations pertaining to preoperative immunochemotherapy and conventional chemotherapy in the context of limited-stage small-cell lung cancer (LS-SCLC) patients. This study conducted a comprehensive comparative assessment concerning the safety and efficacy profiles of preoperative immunochemotherapy and chemotherapy in individuals diagnosed with stage I–IIIB SCLC. Methods This investigation collected 53 consecutive patients diagnosed with LS-SCLC spanning stage I to IIIB who underwent preoperative immunochemotherapy or conventional chemotherapy at our hospital from January 2019 to July 2021. Patients were allocated to receive 2–4 cycles of neoadjuvant immunochemotherapy or chemotherapy, with each cycle lasting three weeks. Comprehensive analyses encompassed baseline characteristics, clinical staging, tumor response, intraoperative and postoperative outcomes, and the assessment of treatment-related adverse events (trAEs). The follow-up period is extended for a minimum of one year after surgery. The primary endpoint embraced the evaluation of the pathological response [major pathological response (MPR) and pathological complete remission (pCR)], while secondary endpoints encompassed objective response rate (ORR), trAEs, surgical resection rates, and disease-free survival (DFS). Results The objective response rate of the immunochemotherapy group was 89.5%, while that of the chemotherapy group was 75.0% (P = 0.206). A total of 19 patients underwent surgery among these 53 patients, with 14 patients in the neoadjuvant chemoimmunotherapy group and 5 patients in the chemotherapy group. And the surgical resection rate of the immunochemotherapy group was 48.3% (14/29), which was higher than the chemotherapy group (20.8%, 5/24, P = 0.038). The rate of MPR in the immunochemotherapy group was 57.1% (8/14) and 40.0% (2/5) in the chemotherapy group (P = 0.891). The rates of pCR in the immunochemotherapy and chemotherapy group were 50.0% (7/14) and 0.0% (0/5), respectively (P = 0.106).The median DFS for both groups were not reached (P = 0.43). The 2-year DFS rate was 21.4% for the immunochemotherapy group versus 40.0% for the chemotherapy group. There was no significant difference in the incidence of grade 3–4 adverse events between the immunochemotherapy group and the chemotherapy group. Conclusions For patients with stage I–IIIB SCLC, neoadjuvant immunochemotherapy is feasible and safe. Although immunochemotherapy did not significantly associated with longer DFS versus chemotherapy alone in patients with stage I–IIIB SCLC, it can produce significant downstaging and increase the possibility of surgery.